Pengaruh gaya kepimpinan ke atas orientasi keusahawanan dengan prestasi perniagaan usahawan mikro bumiputera di Kedah - Hasrul, Hashom (2016)
Micro Enterprenuership is one of the Small and Medium Enterprises (SMEs) that is actively growing and has the ability to help the projection of income both to the society and to the country. Moreover, through the Federal Expenditure Budget 2016, the government has put this group into their main consideration via the increasing of the outlay and financing packages. However, there are less research regards to micro enterprenuership which may help the financial sectors to comprehend the needs of helping this group. This research is performed to identify factors of enterprenuership orientation which enable the business performances and the influence of leaderhip styles; transformational and transactional. This includes dependent variables of business performance, independent variables of enterprenuership orientation and the influence of moderating variables. The research has been conducted via mailing process and based on simple random sampling technique. Through this, there were positive significances between business orientation and risk taken by the enterprenuers. In addition, the research has found that, there are influence of moderating variables of transformational leadership styles on the risk factor and business performances. Furthermore, it is also found that, transactional leadership style also significant in affecting the relationship between the variables of entrepreneurial risk-taking to business performance. The execution of this research involved 81 samples of SMEs micro entrepreneurs in the state of Kedah, Malaysia. This study shall provide empirical feedback to the authority which help them to have in-depth understanding of these entrepreneurs in achieving better achievement.